International Scientific Conference »Research and Education in Nursing«: Book of Abstracts, June 9th 2022, Maribor, Slovenia (University of Maribor Press, 2022)
University of Maribor Faculty of Health Sciences is organizing the International Scientific Conference »Research and Education in Nursing«, held on June 9th 2022. E-proceedings of the conference include most recent findings of domestic and foreign researchers and students in higher education, nursing and health sciences. The conference aims to explore explore advances in nursing and health care research as well as research-based education, in Slovenian and international arena. Furthermore, it will provide an opportunity for practitioners and educators to exchange research evidence, models of best practice and innovative ideas.